2014
DOI: 10.2217/pme.13.95
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Using Diagnostic Next-Generation Sequencing in the Clinical Environment for Inherited Retinal Disorders

Wayne IL Davies

Abstract: Visual impairment, and in particular the inherited retinopathies, is a significant problem worldwide. Many disorders are progressive so their early and accurate detection is crucial to the development and application of appropriate disease management and treatment strategies, some of which are currently being tested in clinical trials. Over the past few decades, the identification of genetic causes that mediate many inherited diseases has largely been based on traditional 'Sanger sequencing' and microchip appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…Determining mutant function rapidly and accurately has become increasingly important with the rise of whole genome sequencing, and the ever-expanding rise in gene mutations with an unknown impact on human health. Rhodopsin mutations linked to inherited retinal disease have been used as examples of how many gene mutations discovered in patients are rarely characterized, and that the molecular basis for pathology is poorly understood (Davies 2014;Chiang and Gorin 2016). Animal models and traditional in vitro assays provide detailed information, but they have not kept pace with the hundreds (.350) of rhodopsin mutations identified to date.…”
Section: Characterizing Novel Rhodopsin Mutations With Yeastmentioning
confidence: 99%
“…Determining mutant function rapidly and accurately has become increasingly important with the rise of whole genome sequencing, and the ever-expanding rise in gene mutations with an unknown impact on human health. Rhodopsin mutations linked to inherited retinal disease have been used as examples of how many gene mutations discovered in patients are rarely characterized, and that the molecular basis for pathology is poorly understood (Davies 2014;Chiang and Gorin 2016). Animal models and traditional in vitro assays provide detailed information, but they have not kept pace with the hundreds (.350) of rhodopsin mutations identified to date.…”
Section: Characterizing Novel Rhodopsin Mutations With Yeastmentioning
confidence: 99%
“…23 Several researchers have investigated the diagnostic yield of MPS technologies in patients with a variety of inherited retinal dystrophies. Using exome sequencing, Xu et al 28 found known or likely deleterious variants in 79 of 157 (50%) of families with RP, representing autosomal-dominant, autosomal-recessive, and X-linked patterns of inheritance.…”
Section: Diagnostic Yield Of Mps Testingmentioning
confidence: 99%
“…Similarly, a detection rate of ~50-70% with MPS technologies was noted in several previous studies. 1,17,23 Most recently, Corton et al, 29 using exome sequencing, found causative variants in 10 of 12 families (83%), with a variety of clinical phenotypes, including RP, Usher syndrome, choroideremia, and Stargardt disease. Using NGS gene panels containing 163 genes previously known to be associated with syndromic and nonsyndromic retinopathies, Wang et al 30 found a causative mutation in 37% of 123 patients with RP.…”
Section: Diagnostic Yield Of Mps Testingmentioning
confidence: 99%
See 2 more Smart Citations